2017
DOI: 10.3390/ijerph14060564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Dietary Intake of Cadmium, Lead and Mercury and Its Relationship with Bone Health among Postmenopausal Women in Spain

Abstract: Background: Heavy metals, such as lead, cadmium, and mercury, are absorbed through contaminated food sources and water. Few studies have investigated the extent to which dietary heavy metals are associated with low bone mineral density. Aims: We aimed to characterize the dietary intake of the heavy metals lead, cadmium and mercury among healthy, non-smoking postmenopausal women in Spain. Furthermore, we sought to establish a putative relationship between bone health and the intake of these heavy metals in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…The dietary exposures for cadmium (2.6 μg/day), mercury (10 μg/day), and lead (8.4 μg/day) in this region were below the values observed in our sample. Regardless, our results are consistent with those from preceding investigations in Spain, indicating that dietary exposures of cadmium, lead and mercury in the Spanish diet are often within the recommendations [ 10 , 39 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. One study estimated the dietary intake of the considered heavy metals [ 63 ] in our region and determined that our area revealed one of the lowest dietary exposures to cadmium and the highest dietary exposure of mercury in Spain; we admit that it is possible that the dietary patterns of our region have changed since then, and changes in the dietary exposures of cadmium, lead and mercury in our region might arise.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The dietary exposures for cadmium (2.6 μg/day), mercury (10 μg/day), and lead (8.4 μg/day) in this region were below the values observed in our sample. Regardless, our results are consistent with those from preceding investigations in Spain, indicating that dietary exposures of cadmium, lead and mercury in the Spanish diet are often within the recommendations [ 10 , 39 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. One study estimated the dietary intake of the considered heavy metals [ 63 ] in our region and determined that our area revealed one of the lowest dietary exposures to cadmium and the highest dietary exposure of mercury in Spain; we admit that it is possible that the dietary patterns of our region have changed since then, and changes in the dietary exposures of cadmium, lead and mercury in our region might arise.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that our participants had figures well below the PTWI for lead. Our findings (4.82 μg/kg b.w./w) are consistent with those from previous studies in Spain [ 39 , 54 , 55 ] that assessed the dietary exposure of heavy metals. The results achieved, in regard to the average dietary exposure of lead in those studies, ranged from 4 μg/kg b.w./w to 56 μg/kg b.w./w between the zones considered.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In a U.S. study, FFQ estimated a mean dietary Cd intake of 10.4 μg/day (range: 1.74–31.6 μg/day) in women who participated in the Women’s Health Initiative [ 16 , 17 , 18 ]. In Spain, the mean for dietary intake derived from FFQ was 29.87 μg/day (range: 20.41–41.04 μg/day) for postmenopausal women and 25.29 μg/day (range: 18.62–35 μg/day) for premenopausal women [ 19 , 20 ]. In Japan, the mean Cd intake that was estimated by the FFQ was 26.4 μg/day in one study [ 21 ].…”
Section: Cadmium Sources and Intake Estimatesmentioning
confidence: 99%